2009
DOI: 10.1016/j.ecresq.2008.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and linguistic diversity in early childhood teacher preparation: The impact of contextual characteristics on coursework and practica

Abstract: CHIH-ING LIM: Cultural and Linguistic Diversity in Early Childhood Teacher Preparation:The Impact of Contextual Characteristics on Coursework and Practica (Under the direction of Kelly Maxwell)The population of children in early childhood settings is becoming increasingly culturally and linguistically diverse, and these changes in demographics have warranted teachers becoming more culturally responsive and better prepared to work with diverse young children and families. Teacher preparation programs across the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 29 publications
(43 reference statements)
1
7
0
Order By: Relevance
“…Preservice teachers of color often feel marginalized or isolated within their preparation programs (Brown, 2014). Universities with fewer faculty of color in their educator preparation programs offer fewer courses about cultural competency (Lim et al, 2009), reinforcing the idea that educators of color (at all educational levels) bear the responsibility of initiating and continuing discussions of race, racism, and privilege. In fact, teacher education programs may not be prepared to teach such courses anyway (Milner & Howard, 2013) as “softer” approaches—those referring to diversity and/or multiculturalism—”assure little to no meaningful discussions of racism, power, and whiteness and how the privileges and benefits that accrue from these systems thwart the very efforts underway to truly produce a teaching force equipped for diverse classrooms” (Cross, 2005, p. 265).…”
Section: Discussionmentioning
confidence: 99%
“…Preservice teachers of color often feel marginalized or isolated within their preparation programs (Brown, 2014). Universities with fewer faculty of color in their educator preparation programs offer fewer courses about cultural competency (Lim et al, 2009), reinforcing the idea that educators of color (at all educational levels) bear the responsibility of initiating and continuing discussions of race, racism, and privilege. In fact, teacher education programs may not be prepared to teach such courses anyway (Milner & Howard, 2013) as “softer” approaches—those referring to diversity and/or multiculturalism—”assure little to no meaningful discussions of racism, power, and whiteness and how the privileges and benefits that accrue from these systems thwart the very efforts underway to truly produce a teaching force equipped for diverse classrooms” (Cross, 2005, p. 265).…”
Section: Discussionmentioning
confidence: 99%
“…All respondents showed the same exposure to all three characteristics. The lack of difference in characteristics for diversity between HBCUs and non-HBCUs was consistent with previous research that found proportionately equal number of courses on cultural diversity between HBCUs and non-HBCUs (Lim et al, 2009), and inconsistent with Marchitello and Trinidad (2019), who found that HBCUs were more effective in preparing teachers to successfully work with marginalized communities due to their curricula design that emphasized supporting the educational needs of marginalized students.…”
Section: Comparison Of Hbcu and Non-hbcu Institutionssupporting
confidence: 89%
“…When this survey was repeated 5 years later with a national sample of programs, there was only minor change; 15% of bachelor's degree programs and 13% of associate degree programs reported requiring an entire course or more in the subject area of "working with bilingual children learning English as a second language" (Maxwell, Lim, & Early, 2006, p. 12). Lim, Maxwell, Able-Boone, and Zimmer (2009) did find that individual early childhood program requirements for course coverage in linguistic diversity were more variable when compared to course coverage in general cultural diversity. Only 14% of institutions required an entire course or more focused on linguistic diversity, while 47% required a course or more focused on general cultural diversity Downloaded by [University of Otago] at 12:56 25 July 2015 (Lim et al, 2009)-which, as indicated earlier, is not considered sufficient to effectively address the learning needs of DLLs.…”
Section: The Standards Context and Teacher Preparationmentioning
confidence: 88%
“…Lim, Maxwell, Able-Boone, and Zimmer (2009) did find that individual early childhood program requirements for course coverage in linguistic diversity were more variable when compared to course coverage in general cultural diversity. Only 14% of institutions required an entire course or more focused on linguistic diversity, while 47% required a course or more focused on general cultural diversity Downloaded by [University of Otago] at 12:56 25 July 2015 (Lim et al, 2009)-which, as indicated earlier, is not considered sufficient to effectively address the learning needs of DLLs.…”
Section: The Standards Context and Teacher Preparationmentioning
confidence: 88%